Cost-effectiveness analysis of implantable cardiac devices in patients with systolic heart failure: a US perspective using real world data. (2nd July 2020) - Shah, Dhvani; Lu, Xiaoxiao; Paly, Victoria F.; Tsintzos, Stelios I.; May, Damian M.
Abstract: Aims: Heart failure with reduced ejection fraction (HFrEF) has a substantial impact on costs and patients' quality-of-life. This study aimed to estimate the cost-effectiveness of implantable cardioverter defibrillators (ICD), cardiac resynchronization therapy pacemakers (CRT-P), cardiac resynchronization therapy defibrillators (CRT-D), and optimal pharmacologic therapy (OPT) in patients with HFrEF, from a US payer perspective. Materials and methods: The analyses were conducted by adapting the UK-based cost-effectiveness analyses (CEA) to the US payer perspective by incorporating real world evidence (RWE) on baseline hospitalization risk and Medicare-specific costs. The CEA was based on regression equations estimated from data from 13 randomized clinical trials ( n = 12, 638). Risk equations were used to predict all-cause mortality, hospitalization rates, health-related quality-of-life, and device-specific treatment effects (vs. OPT). These equations included the following prognostic characteristics: age, QRS duration, New York Heart Association (NYHA) class, ischemic etiology, and left bundle branch block (LBBB). Baseline hospitalization rates were calibrated based on RWE from Truven Health Analytics MarketScan data (2009–2014). A US payer perspective, lifetime time horizon, and 3% discount rates for costs and outcomes were used. Benefits were expressed as quality-adjusted life-years (QALYs). Incremental cost-effectiveness analysis was conducted for 24 sub-groups based on LBBB status, QRS duration, and NYHA class. Results: Results of the analyses show that CRT-D was the most cost-effective treatment at a 100, 000/QALY threshold in 14 of the 16 sub-groups for which it is indicated. Results were most sensitive to changes in estimates of hospitalization costs. Limitations: Study limitations include small sample sizes for NYHA I and IV sub-groups and lack of data availability for duration of treatment effect. Conclusions: CRT-D has higher greater cost-effectiveness across more sub-groups in the indicated patient populations against as compared to OPT, ICD, and CRT-P, from a US payer perspective.